Sensitivity to immune checkpoint inhibitors in BRAF/MEK inhibitor refractory melanoma - Grant A McArthur; Reem Saleh; Lorey Smith; Karen E Sheppard; Riyaben P Patel; Lydia Rui Jia Lim; Darius Schenk; Michael K Lee; Emily Lelliott; Aparna D Rao; Shaghayegh Arabi; Anna S Trigos; et al. (Journal for ImmunoTherapy of Cancer)
Background Resistance to BRAF and MEK inhibitors (BRAFi/MEKi) in metastatic melanoma frequently results in cross-resistance to immune checkpoint inhibitors (ICI), limiting effective treatment options. However, a subset of BRAFi/MEKi-resistant patients remains responsive to second-line ICI, suggesting heterogeneous underlying resistance mechanisms. This study aimed to explore the tumor immune microenvironment in BRAFi/MEKi-resistant melanoma to uncover factors influencing sensitivity to second-line ICI therapy.Method To investigate mechanisms underlying resistance and responsiveness to second-line ICIs, BRAFi/MEKi-resistant melanoma mouse models were used. Flow cytometry was employed to analyze immune cell populations within the tumor microenvironment, focusing on changes in CD8+T effector cells and other key immune subsets. RNA sequencing was performed to profile transcriptomic changes in resistant tumors, providing insights into the signaling pathways associated with resistance. Clinical samples from BRAFi/MEKi-resistant patients were further evaluated for correlations between immune profiles and key signaling pathways to support findings from the preclinical models.Results Using BRAFi/MEKi-resistant melanoma mouse models, we observed distinct alterations in the tumor-immune microenvironment. Tumors exhibiting resistance showed a significant increase in CD8+T effector cells following BRAFi/MEKi treatment, suggesting an immune-stimulatory response. Mechanistic analysis identified the activation of the EGFR-STAT signaling pathway as a key driver of intrinsic resistance in these models. Notably, these tumors retained sensitivity to second-line ICI therapy, contrasting with NRAS-driven BRAFi/MEKi-resistant tumors, which demonstrated cross-resistance to ICIs. Supporting these findings, clinical samples from BRAFi/MEKi-resistant patients revealed a correlation between elevated EGFR activation and higher immune scores, indicating potential sensitivity to ICI therapy in this subset of patients.Conclusion EGFR overexpression emerges as a potential predictive biomarker for responsiveness to second-line ICIs in BRAFi/MEKi-resistant melanoma. These findings underscore the need for stratified therapeutic approaches and highlight EGFR as a target for improving outcomes in ICI therapy.